Nannofossil and stable isotope record across the Paleocene/Eocene Thermal Maximum in ODP Hole 183-1135A - Shijun Jiang; Sherwood W Wise (PANGAEA, 2009)
The Paleocene/Eocene Thermal Maximum (PETM, ca. 55 Ma) is an abrupt, profound perturbation of climate and the carbon cycle associated with a massive injection of isotopically light carbon into the ocean–atmosphere system. As such, it provides an analogue for understanding the interplay between phytoplankton and climate under modern anthropogenic global-warming conditions. However, the accompanying enhanced dissolution poses uncertainty on the reconstruction of the affected ecology and productivity. We present a high-resolution record of bulk isotopes and nannofossil absolute abundance from Ocean Drilling Program (ODP) Site 1135 on the Kerguelen Plateau, Southern Indian Ocean to quantitatively constrain for the first time the influence of dissolution on paleoecological reconstruction. Our bulk-carbonate isotope record closely resembles that of the classic PETM site at ODP Site 690 on the opposite side of the Antarctic continent, and its correlation with those from ODP Sites 690, 1262 and 1263 records allows recognition of 14 precessional cycles upsection from the onset of the carbon isotopic excursion (CIE). This, together with a full range of common Discoasteraraneus and an abundance crossover between Fasciculithus and Zygrhablithusbijugatus, indicates the presence of the PETM at Site 1135, a poorly known record with calcareous fossils throughout the interval. The strong correlation between the absolute abundances of Chiasmolithus and coccolith assemblages reveals a dominant paleoecological signal in the poorly preserved fossil assemblages, while the influence of dissolution is only strong during the CIE. This suggests that r-selected taxa can preserve faithful ecological information even in the severely-altered assemblages studied here, and therefore provide a strong case for the application of nannofossils to paleoecological studies in better-preserved PETM sections. The inferred nannoplankton productivity drops abruptly at the CIE onset, but rapidly increases after the CIE peak, both of which may be driven by nutrient availability related to ocean stratification and vertical mixing due to changed sea-surface temperatures.
Supplement to: Jiang, S; Wise, SW (2009): Distinguishing the influence of diagenesis on the paleoecological reconstruction of nannoplankton across the Paleocene/Eocene Thermal Maximum: An example from the Kerguelen Plateau, southern Indian Ocean. Marine Micropaleontology, 72(1-2), 49-59, https://doi.org/10.1016/j.marmicro.2009.03.003